2010
DOI: 10.1111/j.1466-769x.2010.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The fictionalist paradigm

Abstract: The fictionalist paradigm is introduced, and differentiated from other paradigms, using the Lincoln & Guba template. Following an initial overview, the axioms of fictionalism are delineated by reference to standard metaphysical categories: the nature of reality, the relationship between knower and known, the possibility of generalization, the possibility of causal linkages, and the role of values in inquiry. Although a paradigm's 'basic beliefs' are arbitrary and can be assumed for any reason, in this paper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In the same way, although the blurb says that I “suggest alternatives to PQR” specifically , Giorgi claims that I propose “an alternative to qualitative research” as a whole —because that is what a mathematically minded “empiricist” would do (it is well known that “empiricists” object to qualitative data on principle). Again, although I discuss recent philosophy of science in the final chapter and in several footnotes, and although I have published work on this topic before (Paley, , , , ), Giorgi claims I am “completely insensitive to the discussions that historians and philosophers of science have concerning how scientific communities function”—because “empiricists” draw on positivist philosophy, and know nothing of Kuhn, Feyerabend, Hanson, or Lakatos.…”
Section: Hermetic Epistemologymentioning
confidence: 99%
“…In the same way, although the blurb says that I “suggest alternatives to PQR” specifically , Giorgi claims that I propose “an alternative to qualitative research” as a whole —because that is what a mathematically minded “empiricist” would do (it is well known that “empiricists” object to qualitative data on principle). Again, although I discuss recent philosophy of science in the final chapter and in several footnotes, and although I have published work on this topic before (Paley, , , , ), Giorgi claims I am “completely insensitive to the discussions that historians and philosophers of science have concerning how scientific communities function”—because “empiricists” draw on positivist philosophy, and know nothing of Kuhn, Feyerabend, Hanson, or Lakatos.…”
Section: Hermetic Epistemologymentioning
confidence: 99%
“…Each paradigm therefore has its own quality beacon. For example, the paradigm of fictionalism seeks ‘emotional cadence’ (Paley, 2011). While fictionalism is not particularly useful to most researchers it is impossible to discount as a worldview.…”
Section: Paradigmsmentioning
confidence: 99%
“…This is a significant and worthwhile step, and is one CA has taken. However, earlier in his paper (p. 53) Paley (2011) suggested that pragmatism may transcend these paradigm distinctions altogether, and this is therefore a debate worth pursuing to see if it is possible to escape the confines of paradigmatic presuppositions.…”
Section: Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the papers I've had published in Nursing Philosophy , “The fictionalist paradigm” (Paley, ) is quite possibly my favourite. This view is obviously not widely shared—the paper has a grand total of four citations, one of them by me—but that is one of the reasons I have an affection for it.…”
mentioning
confidence: 99%